2004
DOI: 10.1007/s10350-003-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study on the Effects of Visual Biofeedback and Muscle Training as a Therapeutic Modality in Pelvic Floor Dyssynergia and Slow-Transit Constipation

Abstract: In our experience, patients with pelvic floor dyssynergia are likely to have continued benefit from biofeedback training in the time course, whereas its effects on slow-transit constipation seems to be maximal in the short-term course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
76
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 25 publications
4
76
0
17
Order By: Relevance
“…Biofeedback treatment is an effective option for patients with OD (5,6,23), as was also recently demonstrated by controlled trials (9,10,24), and the present study confirmed this. In fact, 94% of our patients undergoing this training had a successful response, al least in the short term; however, there is evidence of a sustained response of up to two years in up to 80% of patients (9).…”
Section: Discussionsupporting
confidence: 90%
“…Biofeedback treatment is an effective option for patients with OD (5,6,23), as was also recently demonstrated by controlled trials (9,10,24), and the present study confirmed this. In fact, 94% of our patients undergoing this training had a successful response, al least in the short term; however, there is evidence of a sustained response of up to two years in up to 80% of patients (9).…”
Section: Discussionsupporting
confidence: 90%
“…After 6-session manometric-biofeedback protocol (B), maximal and mean strenght increased to 48 and 7 mmHg, respectively. ficacy in short term, measured by QoL scales and by psychological state (28). However, in the long term, follow-up studies indicate a fading effect over time (28).…”
Section: Discussionmentioning
confidence: 99%
“…ficacy in short term, measured by QoL scales and by psychological state (28). However, in the long term, follow-up studies indicate a fading effect over time (28). Even though, a high percentage of patients (up to 50%) continue to report satisfaction even after 12 to 44 months since treatment (29).…”
Section: Discussionmentioning
confidence: 99%
“…Heymen et al (10) dynamics, which is a contraction of the external anal sphincter and the absence of pelvic floor muscle relaxation (6,21,22). The second mechanism, called PFD, is responsible for approximately 30-50% of cases of functional constipation (5).…”
Section: Discussionmentioning
confidence: 99%